Daya Gabung dan Heterobeltiosis Karakter Pertumbuhan dan Hasil Beberapa Galur Backcross Cabai Merah Toleran CMV pada Kondisi Terinokulasi - Herison, Catur; ,, Rustikawati; Handajaningsih, dan Merakati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
ABSTRACTInformation on combining ability and heterosis are desirable to determine the best parents in chili pepper hybrid variety development. To estimate general and specific combining abilities and  heterobeltiosis of backcross lines selected for CMV tolerance, eight selected lines were crossed to three CMV tolerant lines in a Line x Tester method and the crosses were evaluated in a CMV inoculated condition. The results showed that general and specific combining abilities varied tremendously among crosses and traits. Generally, specific combining ability (sca) variances were higher than general combining ability (gca) variance indicating that interaction of non-aditive predominance the inheritance of traits under study. Amongs lines evaluated, there was no a general combiner line for vegetative growth. However, lines S1B3A-29-13-47 and S1B3B-12-13-2 were the best general combiner for a breeding program to improve total number of fruits and fruit weight per plant, respectively. Crosses of S1B3C-16-22-34 x C1042, S1B3B-49-40-6 x C1043, and S1B3C-34-18-9 x C1042 were consedered the most prospective crosses as indicated by high value of sca, i.e., 130.53, 102.01 and 61.93, with heterobeltiosis estimate of 146.06, 26.05 and 24.31, respectively.Keywords: capsicum annuum, heterobeltiosis, GCA, SCA